Text comprehension strategies and their effectiveness in the classroom - Castro Pedraza, Adriana; Paez Castiblanco, Nidia Jazmín (Rastros Rostros, 2015)
Introduction: this article presents the results of a research project entitled “El mundo de la lectura: estrategias para la comprensión” [The world of reading: comprehension strategies] attached to the Language Pedagogy line of the Master’s in Linguistics at the Universidad Pedagógica y Tecnológica de Colombia (uptc), whose topic revolves around difficulties in reading comprehension of fourth and fifth graders and some improvement alternatives. It was conducted at the Institución Educativa Juan José Neira in Machetá, Cundinamarca, Colombia. Methodology: this study used the methodology of Participatory Action Research and was conducted in three phases: 1) diagnosis, 2) design, and 3) implementation of the proposal and assessment, each with the participation of teachers. Results: an educational intervention proposal aimed at improving reading comprehension of students by creating teaching units was designed. Conclusions: a significant improvement rate was evident in comprehension strategies used by the students, which could be established through a comprehension test applied during assessment. Moreover, the collaborative work of teachers and the construction of a guide presenting general strategies that can be ap